(3GdfXe GdEbJUGOjI GdeYGUQI (B:s (3YQV hJMdjd hfbO (B/s - (3YHO Gddg, eMeO MGeOs ((3GdQjGV(B: s (3YeGOI TDhf GdecJHGJ(B, s, 1987)
(3GdfXGe GdEbJUGOj hCSS Jbhjeg(B- (3GdfXGe GdEbJUGOj GdQCSeGdj(B- (3fXGe GdJNWjW GdeQcRj(B- (3GdfXGe GdEbJUGOj GdeNJdW(B- (3GdfXe GdEbJUGOjI aj GdOhd GdfGejI(B.s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdeYGUQs; (3GdfXe GdEbJUGOjIs